Regulators of homologous recombination repair as novel targets for cancer treatment - Krajewska, Małgorzata; Fehrmann, Rudolf S. N.; de Vries, Elisabeth G. E.; van Vugt, Marcel A. T. M. (Frontiers in Genetics, 2015)
To cope with DNA damage, cells possess a complex signaling network called the ‘DNA damage response’ (DDR), which coordinates cell cycle control with DNA repair. The importance of this network is underscored by the cancer predisposition that frequently goes along with hereditary mutations in DNA repair genes. One especially important DNA repair pathway in this respect is homologous recombination (HR) repair. Defects in HR repair are observed in various cancers, including hereditary breast and ovarian cancer. Intriguingly, tumor cells with defective HR repair show increased sensitivity to chemotherapeutic reagents, including platinum-containing agents. These observations suggest that HR-proficient tumor cells might be sensitized to chemotherapeutics if HR repair could be therapeutically inactivated. HR repair is an extensively regulated process, which depends strongly on the activity of various other pathways, including cell cycle pathways, protein-control pathways and growth factor-activated receptor signaling pathways. In this review, we discuss how the mechanistic wiring of HR is controlled by cell-intrinsic or extracellular pathways. Furthermore, we have performed a meta-analysis on available genome-wide RNA interference studies to identify additional pathways that control HR repair. Finally, we discuss how these HR-regulatory pathways may provide therapeutic targets in the context of radio/chemosensitization.